Approach of detecting LDoS attack based on time window statistic - WU Zhi-jun; ZENG Hua-long; YUE Meng (Tongxin xuebao)
Through analysised of normal traffic and attack flow,statistic result showed that the normal traffic throughout had an obviously degrade and attack flow had a short time abnormity pulse with higher amplitude.An approach of de-tecting LDoS attack based on time window statistic was presented.Experiments on different length of sample time were conducted in a test environment established on simulation network.Test results show that the detection probability is more than 96%,false negative and false positive are less than 3%.